A study on the customer satisfaction toward agent services at MCIS Zurich Melaka Branch / Nor Asmarina Abu Bakar - Abu Bakar, Nor Asmarina (Faculty of Business and Management, 2011)
Insurance agent is a person who is responsible for responding to customer inquiries and making sure that any problems they are experiencing are resolved. They are work on behalf customer and must make sure that all needs and customer’s desire are fulfilled and satisfied. Customer satisfaction is important to determine successfulness of one company. If customer do not satisfy with company services or product that means the company should find a solution to solve and try to fulfil their customers need. The thrust of this study is directed towards answering the question regarding several factors that have a significant relationship to the customer satisfaction toward agent services at MCIS Zurich Melaka Branch where it is conducted at MCIS Zurich Melaka at Jalan Munshi Abdullah, Melaka. The researcher had gained the information via questionnaire which selects 50 customers as the respondents. In this study, researcher use convenient sampling in selecting the respondent. From this study, it is found that all the factors listed have a significant relationship with to the customer satisfaction toward agent services at MCIS Zurich Melaka Branch. Besides that, the MCIS Zurich Melaka Branch’s management should take an effort to make sure that their customer is always satisfied with their agent’s services in order to increase the profit and have a good reputation in insurance industry.